A spirited workplace: employee perspectives on the meaning of workplace spirituality - Van Tonder, Christian Louis; Ramdass, P. (OpenJournals Publishing, 2009)
Although views on the nature of workplace spirituality abound, the meaning of the concept and its relatedness to other organisational constructs are everything but clear. Using a qualitative approach, the current study set out to explore the meaning of workplace spirituality among a group comprising 31 employees of a South African manufacturing concern. The findings derived through content analysis align well with literature perspectives on the phenomenon. The findings however also reveal that employee awareness and understanding of workplace spirituality are limited.